2008
DOI: 10.1177/1933719108324134
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Trioxide (As2O3) Inhibits Expression of Estrogen Receptor—alpha Through Regulation of the Mitogen-activated Protein Kinase (MAPK) Pathway in Endometrial Cancer Cells

Abstract: Given that prolonged exposure to unopposed estrogen has been implicated in endometrial carcinogenesis, our goal was to evaluate the effect of As(2)O(3) on regulation of estrogen receptor-alpha (ERa) expression in endometrial cancer cells. As(2)O(3) inhibited ER- mRNA and protein expression in a dose-dependent manner in both the Ishikawa and ECC-1 endometrial cancer cell lines. Treatment with As(2)O(3) resulted in rapid phosphorylation of the p42/p44 MAPK which could be abolished by addition of the MAPK inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…In this study, we found that CCND1 was upregulated in most of the tumor types (Figure 6). Meanwhile, ATO has been demonstrated to be an inducer of JUN through regulating JNK and MAPK pathways in many cancers, such as bladder cancer [67], prostate cancer [68], NSCLC [69], liver cancer [70] and endometrial cancer [71]. Here, JUN was downregulated in almost all tumor types in our pan-cancer analysis (Figure 6).…”
Section: Resultsmentioning
confidence: 75%
“…In this study, we found that CCND1 was upregulated in most of the tumor types (Figure 6). Meanwhile, ATO has been demonstrated to be an inducer of JUN through regulating JNK and MAPK pathways in many cancers, such as bladder cancer [67], prostate cancer [68], NSCLC [69], liver cancer [70] and endometrial cancer [71]. Here, JUN was downregulated in almost all tumor types in our pan-cancer analysis (Figure 6).…”
Section: Resultsmentioning
confidence: 75%
“…Cell line experiments demonstrated that the methylation levels of LINE-1 were decreased by treatment with estradiol but not with dihydrotestosterone [57]. Arsenic exposure has been reported to have endocrine-disruptive effects [58, 59], and it may thus be likely that arsenic causes hypomethylation through its endocrine-disrupting activity.…”
Section: Discussionmentioning
confidence: 99%
“…These successful cases prompted investigations to elucidate the mechanisms of action underlying these clinical responses. Proposed mechanisms for ATO's antitumorigenic effects include induction of apoptosis through its effects on caspases, inhibition of cell growth through its interactions with multiple signaling pathways including the mitogen‐activated protein kinase pathway, promotion of cell differentiation, and inhibition of angiogenesis via downregulation of vascular endothelial growth factor production 9,10 . In spite of its efficacy in various cancers, ATO is also a toxic agent: chronic exposure to ATO has resulted in numerous pathogeneses such as lung cancer, peripheral nerve effects and cardiovascular changes 11–13 .…”
Section: Introductionmentioning
confidence: 99%
“…Proposed mechanisms for ATO's antitumorigenic effects include induction of apoptosis through its effects on caspases, inhibition of cell growth through its interactions with multiple signaling pathways including the mitogen-activated protein kinase pathway, promotion of cell differentiation, and inhibition of angiogenesis via downregulation of vascular endothelial growth factor production. 9,10 In spite of its efficacy in various cancers, ATO is also a toxic agent: chronic exposure to ATO has resulted in numerous pathogeneses such as lung cancer, peripheral nerve effects and cardiovascular changes. [11][12][13] In some studies, the ATO concentrations required to take effect were much higher than the physiologically tolerable concentrations, which limited its clinical application.…”
Section: Introductionmentioning
confidence: 99%